Becker’s Coefficient as a Tool of Measuring Gender Disparities: Analysis of Literacy in India - M.S. Swapna and G.S. Premkumarar (International Journal of Social and Economic Research, 2012)
United Nations Development Programmes has given at most importance to inequality analysis in its human development report 2010. It has paved greater ways and scope for further understanding and analysing width and depth of inequalities in all the spares of development. In this regard the present work is an attempt to analyse the gender disparities in educational development of India. For the purpose we have used decadal time series census data from the period 1981 to 2011. Becker’s coefficient was used to measure the extent of discrimination exist in literacy level in Indian states. Discriminate coefficient can take any value from zero to infinity. Higher the discriminate value, higher is the discrimination and vice versa. We have analysed gender discrimination in literacy for major seventeen Indian states including Jammu Kashmir and Delhi. It is found from the study that the discrimination has reduced over the period of time but still exists. Mean time the higher discriminate value is registered in the economically backward states like, Bihar, Rajasthan and Uttar Pradesh. The lower discriminate value is registered in Kerala which is got highest rank in human development of India and Delhi which is the capital city of India. The discriminate value is moderate in remaining other states. Hence economic and human developments are prerequisite for reducing gender disparity in Indian education system in general and literacy in particular.